Power, Curriculum, and Embodiment Re-thinking Curriculum as Counter-Conduct and Counter-Politics - Burns, James P. (Curriculum Studies Worldwide, 2018)
This book explores curriculum inquiry through the theoretical lens of governmentality as a site of disciplinary biopolitics and a system of heteropatriarchal political economy. Examining the powerscape in which education is currently situated, the author offers a conceptual framework for curriculum scholarship based on Foucault's genealogy of power, and analyzes how curriculum design has historically effectuated disciplinary power on students and teachers. The book engages in a synoptic essay of the history of American violence, an important curricular issue, and finally applies Foucault's concepts of truth-telling and self-care to curriculum studies as a form of self and social reconstruction in complicated conversation with each other.